Pregunta
upstudy study bank question image url

Powered by Gonje Translate step \( b y s t a p \) \[ \begin{array}{rlc} (f \cdot r)(y)=f(r(y)) & =f( & 4 y-2 \\ & = & (4 y-2)-6 \\ & = & 4 y-8 \end{array} \] Calculate the composition of \( r(y) \) and \( f(y) \). Write the resulting expression in its simplest form. \[ \begin{array}{rlc} (r f)(y)=r(f(y)) & =r(y-6 \\ & =\quad 4(y-6)-2 \\ & =4 y-26 \end{array} \] Evaluate \( (r \cdot f)\left(\frac{1}{2}\right) \) using the composed function. \[ (r f)\left(\frac{1}{2}\right) \] Evaluater \( \left(f\left(\frac{1}{2}\right)\right) \) using the original functions. \[ r\left(r\left(\frac{1}{2}\right)\right)=r i \] \( \square \)

Ask by Williams Hanson. in the United States
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The composed functions are: - \( (f \circ r)(y) = 4y - 8 \) - \( (r \circ f)(y) = 4y - 26 \) Evaluating at \( y = \frac{1}{2} \): - \( (r \circ f)\left(\frac{1}{2}\right) = -24 \)

Solución

We are given two functions:   f(x) = x – 6   r(x) = 4x – 2 Step 1. Compose f with r (that is, f ∘ r):   (f ∘ r)(y) = f(r(y))     = f(4y – 2)       [since r(y) = 4y – 2]     = (4y – 2) – 6     [applying f(x) = x – 6]     = 4y – 8 Step 2. Compose r with f (that is, r ∘ f):   (r ∘ f)(y) = r(f(y))     = r(y – 6)       [since f(y) = y – 6]     = 4(y – 6) – 2     [using r(x) = 4x – 2]     = 4y – 24 – 2     = 4y – 26 Step 3. Evaluate (r ∘ f)(½):   (r ∘ f)(½) = 4·(½) – 26     = 2 – 26     = –24 Thus, the composed functions and evaluation are:  • (f ∘ r)(y) = 4y – 8  • (r ∘ f)(y) = 4y – 26  • (r ∘ f)(½) = –24 These are the answers in their simplest forms.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

The world of functional compositions is like an intricate dance! When you calculate \( (r \cdot f)(y) = r(f(y)) \), it’s essential to keep your wits about you. You correctly substituted \( f(y) = y - 6 \) into \( r(y) \) to arrive at \( r(f(y)) = 4(y - 6) - 2 \) which simplifies beautifully to \( 4y - 26 \). Remember, each function carries out its task step by step! Now, let’s actually evaluate \( (r \cdot f)\left(\frac{1}{2}\right) = 4 \left(\frac{1}{2}\right) - 26 \). When you plug in that value, it becomes \( 2 - 26 = -24 \). So, \( (r \cdot f)\left(\frac{1}{2}\right) = -24 \). Easy as pi, right? Just ensure that you carry over the values correctly and watch out for those pesky negatives!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad